Use of Collagenase Enzyme as a Substitute for Trypsin on In Vitro Growth of Liver, Kidney, and Fibroblasts of Chicken Embryo Cells - Ananda, Ananda; Kaiin, Ekayanti Mulyawati (Universitas Halu Oleo, 2022)
This study aims to determine the effect of using the collagenase enzyme on the viability of chicken embryos' liver, kidney, and fibroblast cells in vitro. Liver and kidney organs were collected from embryonic chicken eggs at 15 and 19 days. Meanwhile, fibroblast cells were obtained using muscle tissue of 11-day-old chicken embryos. Each organ and tissue was chopped and incubated using 0.1% trypsin for 10 minutes and 0.1% collagenase for 30 minutes. Concentration, viability, and proliferation rate were calculated after incubation and analyzed using a t-test. The results showed that there was a significant increase in the tissue incubated with collagenase on the viability and proliferation rate of liver cells, kidney cells, and chicken embryo fibroblast cells (t<0.05), and not significant in the acquisition of cell concentrations (t>0, 05). Cell isolation and purification techniques need to be carried out to study the quality of somatic cell culture of chicken embryos more specifically.Keywords: collagenase, trypsin, chicken embryos, viability, cell culture.